Purification of core-binding factor, a protein that binds the conserved core site in murine leukemia virus enhancers. - Wang, S W (1992)
The Moloney murine leukemia virus causes thymic leukemias when injected into newborn mice. A major genetic determinant of the thymic disease specificity of the Moloney virus genetically maps to two protein binding sites in the Moloney virus enhancer, the leukemia virus factor b site and the adjacent core site. Point mutations introduced into either of these sites significantly shifts the disease specificity of the Moloney virus from thymic leukemia to erythroleukemia (N. A. Speck, B. Renjifo, E. Golemis, T. Frederickson, J. Hartley, and N. Hopkins, Genes Dev. 4:233-242, 1990). We have purified several polypeptides that bind to the core site in the Moloney virus enhancer. These proteins were purified from calf thymus nuclear extracts by selective pH denaturation, followed by chromatography on heparin-Sepharose, nonspecific double-stranded DNA-cellulose, and core oligonucleotide-coupled affinity columns. We have achieved greater than 13,000-fold purification of the core-binding factors (CBFs), with an overall yield of approximately 19%. Analysis of purified protein fractions by sodium dodecyl sulfate (SDS)-polyacrylamide gel electrophoresis reveals more than 10 polypeptides. Each of the polypeptides was recovered from an SDS-polyacrylamide gel, and those in the molecular size range of 19 to 35 kDa were demonstrated to have core-binding activity. The purified CBFs were shown by DNase I footprint analyses to bind the core site in the Moloney virus enhancer specifically, and also to core motifs in the enhancers from a simian immunodeficiency virus, the immunoglobulin mu chain, and T-cell receptor gamma-chain genes.